A rare case of childhood-onset systemic lupus erythematosus associated end-stage renal disease with cerebral abscess and hemorrhage - Jee Hyun Kim; Jae Il Shin; Ji Hong Kim; Keum Hwa Lee (Korean Society of Pediatric Nephrology, 2024)
Systemic lupus erythematosus (SLE) is a chronic autoimmune inflammatory disease that affects multiple organs. More than half of the patients with SLE have kidney involvement, and up to 10% of patients with lupus nephritis develop end-stage renal disease (ESRD). Central nervous system (CNS) involvement in SLE occurs in 21% to 95% of patients. Severe neurological manifestations such as seizures, cerebrovascular disease, meningitis, and cerebrovascular accidents can develop in childhood-onset SLE, but cerebral infections, such as brain abscess and hemorrhage, are seldom reported in lupus nephritis, even in adults. Here, we report a rare case of childhood-onset SLE with ESRD, cerebral abscess, and hemorrhage. A 9-year-old girl diagnosed with lupus nephritis was administered high-dose steroids and immunosuppressant therapy to treat acute kidney injury (AKI) and massive proteinuria. The AKI deteriorated, and after 3 months, she developed ESRD. She received hemodialysis three times a week along with daily peritoneal dialysis to control edema. She developed seizures, and imaging showed a brain abscess. This was complicated by spontaneous cerebral hemorrhage, and she became unstable. She died shortly after the hemorrhage was discovered. In conclusion, CNS complications should always be considered in clinical practice because they increase mortality, especially in those with risk factors for infection.